Mixed alkali effect as a tunable way of controlling the electrical and optical properties of manganese phosphate glasses - Bahrami, Sana (Technium Electro, 2024)
The mixed alkali effect (MAE) can be utilized in tuning various properties of oxide glasses. In this paper, MAE was explored in the electrical and optical properties of new manganese phosphate glasses with the composition 40P2O5–10MnO2–(50-x)Li2O–xRb2O, x= 5, 15, 25, 35, and 45 mol %. Glassy samples were prepared by the conventional melt quenching technique. It was observed that the conductivity in the present glassy system is more ionic rather than electronic. Due to the presence of the MAE, the activation energy varied nonlinearly with Rb2O molar percentage and reached a maximum of 0.93 eV at x= 25 mol%. The optical properties also showed nonlinear variation with Rb2O content, which supported the existence of the MAE in the optical properties.